A rapid slid coagglutination test-an alternative to the fluorescent antibody test for the identification of Neisseria gonorrhoeae. Issue 4 (April 1981) - Shanker, S; Daley, D A; Sorrell, T C
Abstract : The Phadebact(R) Gonococcus Test, a slide coagglutination test, was compared with the Difco fluorescent antibody test for the identification of Neisseria gonorrhoeae isolated from 18- to 24-hour primary plates. A total of 316 morphologically characteristic, oxidase-positive, Gram-negative diplococci were tested. Altogether 298 isolates were identified definitively as N. gonorrhoeae by a rapid carbohydrate utilisation test; 287 of the 298 isolates of N. gonorrhoeae were identified by the coagglutination test, a sensitivity of 96%. The sensitivity of the fluorescent antibody test was 85% (254 of 298 isolates). False-positive results due to cross-reactions with non-gonococcal Neisseria were uncommon (1 of 18 non-gonococcal isolates in the coagglutination test, a specificity of 94%; 2 of 18 in the fluorescent antibody test, a specificity of 88%). None of the 14 other contaminant organisms seen frequently on primary isolation media gave positive reactions. Interpretation of the coagglutination test proved to be difficult initially. Thirty-two (10%) coagglutination tests had to be repeated; 3 of the 32 (1% of the total isolates tested) remained uninterpretable.